The Coherence of the Belief in the Existence of Evil in Traditional Yorùbá Theology: A Process-Relational Analysis - Ofuasia, Emmanuel (Review of ecumenical studies, 2024)
Due to its domineering Western and Christian influence, philosophy of religion, as a discipline, is hesitant or reluctant to entertain arguments on similar subjects from non-Western and non-Christian traditions even when these traditions may have answers to problems or issues in the discipline. Of these problems, the present research will limit its scope to theodicy. Whereas the problem continues to encounter endless debates and attempts to reconciling a loving, powerful and knowledgeable Deity with the existence of natural and moral evils in the world, the lack of coherence in that tradition of thought cannot be said for "Yorùbá theology". Through the method of philosophical and hermeneutical analyses, the effort of this research is to unpack the process underpinning of "Yorùbá theology" which helps in formulating a coherent understanding of the reality of evil in the presence of a good, loving and wise "Olódùmaré" that is void of Satan/Devil. On this note, this research submits, having used Yorùbá process theology as paradigm, that the debate over the problem of evil in mainstream tradition of philosophy of religion may be resolved if non-Western and non-Christian traditions are invited into the discourse.